Identification of bacteria that affect the in vitro establishment of nodal segments of Guadua angustifolia Kunth (Revista de Investigaciones Universidad del Quindío, 2009)
The in vitro culture of nodal segments (medium and basal) of branches chusquines Guadua angustifolia Kunth, has a high degree of bacterial contamination, affecting their micropropagation, in the establishment phase. For identification of the contaminating bacteria, seven groups with aroma and color characteristics were selected, which were applied differential culture media, such as those used for phytopathogenic bacterial genera, such as: YDC, King B, D1 and D5. In addition, biochemical tests were performed to confirm identification such as: gram stain, Hugh and Leifson test, Indol; and motility. This investigation led to the identification of the genera: Xanthomonas, Pseudomonas, Agrobacterium, and Erwinia-Pseudomonas partnership. The genus Pseudomonas was the main pollutant for basal nodal segments (26.8%) and Erwinia-Pseudomonas association for media nodal segments (26.6%). The sensitivity to antibiotics by bacteria, were determined by antibiogram, where genera was found to be sensible to Amikacin, Gentamicin and Vancomycin.
Keywords: in vitro; nodal segments; Guadua angustifolia; plant pathogens; antibiotics